Effects of Variety, Season, and Region on Theaflavins Content of Fermented Chinese Congou Black Tea - Yongwen Jiang; Jinjie Hua; Bei Wang; Haibo Yuan; Haile Ma (Journal of Food Quality)
The effects of variety, region, and season on the theaflavins content of fermented Congou black tea were determined. Fresh tea leaves from 5 varieties, 3 tea-growing regions, and 3 harvesting seasons were treated by withering, rolling, fermenting, and drying. Contents of theaflavins, polyphenol oxidase (PPO), peroxidase (POD), and individual catechins in each treatment process were determined. The results showed that the varieties of Yinghong 9 and Hongyan 12 produced high concentrations of theaflavin, as much as 0.5% and 0.6%, respectively. The production capacity of theaflavin in different regions had the trend of Yingde > Changsha > Hangzhou. Fresh leaves plucked in spring season produced the strongest theaflavins. In tea leaves, high ratio of PPO to POD activity and high contents of certain individual catechins lead to high yield of theaflavin production during the whole process.